MINIREVIEW ON SUSTAINABLE ANTIVIRULENCE STRATEGY FOR AQUACULTURE - Julyantoro, Pande Gde Sasmita; Bossier, Peter; Defoirdt, Tom (Politeknik Kelautan dan Perikanan Jembrana, 2024)
The increasing occurrence of antibiotic-resistant bacteria is one of the major challenges currently faced by the aquaculture sector. Ineffective applications of antibiotics to treat bacterial diseases, leading to the need for alternative strategies to address the problem. The antivirulence approach is a highly promising strategy that aims to stop pathogenic bacteria from causing harm to the host by disrupting their virulence mechanisms. This approach involves understanding the mechanisms of bacterial pathogenicity that can be developed into new therapeutic methods. There have been numerous advancements in combating bacterial infections, such as disrupting host-pathogen communication and inhibiting quorum sensing (QS). Antivirulence therapy offers a significant advantage as it specifically targets bacterial virulence without imposing excessive pressure on bacterial growth, reducing the risk of resistance development. This review outlines the limitations of antibiotic use and presents current insights into bacterial pathogenicity mechanisms and antivirulence strategies in aquaculture. It particularly highlights the impact of host-pathogen signaling via catecholamines, stress hormones, and QS mechanisms in certain aquaculture-pathogenic bacteria. The influence of host stress hormones on pathogen growth and virulence is noteworthy. Quorum sensing (QS) is known to regulate the expression of certain virulence genes in response to bacterial density by releasing and detecting a small signal molecule called autoinducers. This review further explains various strategies to interfere with QS mechanisms, including inhibiting signal molecule biosynthesis, using QS antagonists, chemical inactivation, or biodegradation of QS signals. These promising strategies have been considered as the first step and proof of concept of antivirulence strategies to prevent disease outbreaks in aquaculture.Meningkatnya jumlah bakteri yang resisten terhadap antibiotik merupakan salah satu tantangan besar yang saat ini dihadapi oleh sektor akuakultur. Penerapan antibiotik yang tidak efektif untuk mengobati penyakit bakterial, menyebabkan perlunya strategi alternatif untuk mengatasi masalah tersebut. Pendekatan antivirulensi adalah strategi yang sangat menjanjikan yang bertujuan untuk menghentikan bakteri patogen dalam menyebabkan kerusakan pada inang dengan mengganggu mekanisme virulensinya. Pendekatan ini melibatkan pemahaman mekanisme patogenisitas bakteri yang dapat dikembangkan menjadi metode terapi baru. Terdapat banyak perkembangan dalam melawan infeksi bakteri, seperti mengganggu komunikasi inang-patogen dan menghambat quorum sensing (QS). Terapi antivirulensi menawarkan keuntungan yang signifikan karena secara spesifik menargetkan virulensi bakteri tanpa memberikan tekanan berlebihan pada pertumbuhan bakteri, sehingga mengurangi risiko berkembangnya resistensi. Reviu ini menguraikan keterbatasan penggunaan antibiotik dan menyajikan wawasan terkini mengenai mekanisme patogenisitas bakteri dan strategi antivirulensi dalam budidaya perikanan. Reviu ini terutama menyoroti dampak sinyal patogen inang melalui katekolamin, hormon stres, dan mekanisme QS pada bakteri patogen tertentu dalam akuakultur. Pengaruh hormon stres inang terhadap pertumbuhan dan virulensi patogen patut diperhatikan. Quorum sensing (QS) diketahui mengatur ekspresi gen virulensi tertentu sebagai respons terhadap kepadatan bakteri dengan melepaskan dan mendeteksi molekul sinyal kecil yang disebut autoinduser. Reviu ini lebih lanjut menjelaskan berbagai strategi untuk mengganggu mekanisme QS, termasuk menghambat biosintesis molekul sinyal, menggunakan antagonis QS, inaktivasi kimia, atau biodegradasi sinyal QS. Strategi yang menjanjikan ini telah dianggap sebagai langkah pertama dan bukti dari konsep strategi antivirulensi untuk mencegah wabah penyakit pada budidaya perikanan.